ESTIMATING FACTORS AFFECTING WHEAT MARKETING EFFICIENCY USING TOBIT MODEL - T. , Jassam Q.; Ali, E. H.; Ghaylan, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to measure marketing efficiency and study important factors affecting , using TOBIT qualitative response model for wheat crop in Salahalddin province. Results revealed that independent factors such as (marketing type, crops duration in the field, average marketing cost, distance between farm and marketing center, and average productivity) had an impact on wheat marketing efficiency. This impact varied in size and direction due to value of parameters. Values of marketing efficiency fluctuated within cities and towns in the province. The average value on the province level was 76.75%. This study was recommended developing marketing infrastructures which is essential to efficiency increases. In addition, it is important to decrease routine administrative procedures in governmental marketing institutions and establish marketing centers, even if they will be temporary, in harvesting and marketing period near the production areas.